2001
DOI: 10.1042/0264-6021:3590175
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of mutations in housefly (Musca domestica) acetylcholinesterase involved in insecticide resistance

Abstract: Acetylcholinesterase (AChE) insensitive to organophosphate and carbamate insecticides has been identified as a major resistance mechanism in numerous arthropod species. However, the associated genetic changes have been reported in the AChE genes from only three insect species; their role in conferring insecticide insensitivity has been confirmed, using functional expression, only for those in Drosophila melanogaster. The housefly, Musca domestica, was one of the first insects shown to have this mechanism; here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
173
0
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(193 citation statements)
references
References 28 publications
5
173
0
14
Order By: Relevance
“…Sequence analysis showed a single amino acid substitution Gly328Ala (Torpedo numbering) when the C and Table 4 Amino acid substitutions found in the comparison of the predicted CcaE7 protein of different individuals from the C and the W strains of C. capitata W strains were compared. This mutation is adjacent to the glutamate of the catalytic triad in D. melanogaster (Walsh et al, 2001), and has been associated with insecticide resistance in populations of D. melanogaster, M. domestica and Plutella xylostella (Walsh et al, 2001;Menozzi et al, 2004;Baek et al, 2005;Lee et al, 2007). Individuals with the WR phenotype were homozygous for this mutation, whereas individuals with the WS phenotype were either heterozygous or wild type at this position.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Sequence analysis showed a single amino acid substitution Gly328Ala (Torpedo numbering) when the C and Table 4 Amino acid substitutions found in the comparison of the predicted CcaE7 protein of different individuals from the C and the W strains of C. capitata W strains were compared. This mutation is adjacent to the glutamate of the catalytic triad in D. melanogaster (Walsh et al, 2001), and has been associated with insecticide resistance in populations of D. melanogaster, M. domestica and Plutella xylostella (Walsh et al, 2001;Menozzi et al, 2004;Baek et al, 2005;Lee et al, 2007). Individuals with the WR phenotype were homozygous for this mutation, whereas individuals with the WS phenotype were either heterozygous or wild type at this position.…”
Section: Discussionmentioning
confidence: 95%
“…A total of 14 mutations associated to resistance to insecticides have been reported in AChE in higher Diptera (Mutero et al, 1994;Kozaki et al, 2001;Vontas et al, 2001Vontas et al, , 2002Walsh et al, 2001;Hsu et al, 2006). To investigate whether these or other mutations were present in individuals of the resistant strain, we obtained a coding sequence of the AChE gene for C. capitata (Ccace) from three individuals of each of the three phenotypes investigated, WR, WS and C. Phylogenetic analysis showed that the Ccace gene described here may be designated as an ace2 ortholog according to the nomenclature of Weill et al (2003) as indeed higher Diptera have a single ace gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified AChE from a susceptible housefly was shown to be sensitive to pesticides (Shi et al 2001), and the expressed AChE showed the similar properties with the AChE purified from the body of housefly, therefore, the expression of the ace gene cloned from a housefly strain susceptible to insecticides provided a good choice for isolating AChE. The acetylcholinesterase gene from a wild strain of M. domestica has been expressed in Sf cells, the FLAG-AChE showing enzyme activity, however, the K i of the recombinant enzyme to dichlorovos was only 1.34 lM -1 min -1 (Walsh et al 2001). The K i of our expressed AChE to dichlorovos is 838.6 lM -1 min -1 , much higher than the previously reported FLAG-AChE, suggesting our enzyme is more sensitive to insecticides.…”
Section: Discussionmentioning
confidence: 97%
“…The Trichoplusia ni cell line Tn-5B1-4 has been shown to produce especially high yields of recombinant protein and was even capable of producing small amounts of galactose-terminated N-glycans (Altmann et al 1999). In another previous report (Walsh et al 2001), to reveal the underlying resistance mechanism, the ACheE gene from wild and resistant strains of housefly (Musca domestica) were successfully expressed in insect cell line Sf, and the expressed fusion protein FLAG-AChE showed strong enzyme activity, suggesting that insect cells are suitable for expressing biologically active the housefly AChE.…”
Section: Introductionmentioning
confidence: 97%